Communication—A Simple Empirical Method for Determination of CuOOH/CuO Redox Couple in Electrochemical Nonenzymatic Glucose Sensing. Issue 1 (21st January 2021) - Dung, Nguyen Quoc; Thi Thuy Duong, Tran; Lam, Tran Dai; Dung, Dang Duc; Huy, Nguyen Nhat; Thanh, Dang Van
Abstract : In this work, we introduced a model of glucose reaction at the electrode and determined the reduction potential of CuOOH/CuO redox couple at CuO nanowires/ITO electrode (CNIE) via an empirical study. The cyclic voltage scanning of CNIE to glucose in different concentrations of NaOH electrolyte solution was conducted using the background subtraction (BS-CV) method. By interpolating the glucose concentration to zero based on the curve of glucose concentration versus oxidation potential in different pH media of NaOH, the standard electrode potential of the CuOOH/CuO redox couple was calculated to be +0.433 (V vs SHE).